Secure-Spin with hashing to support mobility and security in wireless sensor network - Amri, Mohammad Hossein (2013)
Routing protocols with supporting mobility is a new area that these years attract many researchers; different protocols made to support different applications and needs. The existing routing protocols with support mobility often designed with no security in mind; so later other researchers tried to add security function to these protocols. Adding new and extra functionality (even security) sometimes brings other vulnerability. The Secure-SPIN is a routing protocol with support mobility that branched from SPIN protocol; the Spin protocol has no security, but Secure-SPIN tries to add security to it. During this extra functionality, the Secure-SPIN keeps its vulnerability to eavesdropping as SPIN does. This thesis tries to secure Secure-SPIN with utilizing hash function (SHA1), and with separating encryption and hash function from each other try to add new security feature. With dividing hash and encryption less or same level of energy will be use. In this thesis, mathematical prove used To prove security of proposed protocol. The proposed solution use extra energy but the energy consumption is low enough to ignore the extra energy usage in tradeoff with more security.